Enhancement of photoluminescence and electrical properties of Ga-doped ZnO thin film grown on alpha-Al2O3(0001) single-crystal substrate by rf magnetron sputtering through rapid thermal annealing - Cho, J; Nah, J; Oh, MS; Song, JH; Yoon, KH; Jung, HJ; Choi, WK (INST PURE APPLIED PHYSICS, 2001)
Ga2O3 (1 wt%)-doped ZnO (GZO) thin films were deposited on alpha -Al2O3(0001) by rf magnetron sputtering at 550 degreesC and a polycrystalline structure was obtained. As-grown GZO thin films show poor electrical properties and photoluminescence (PL). For the improvement of these properties, GZO thin films were annealed at 800-900 degreesC in N-2 atmosphere for 3 min. After rapid thermal annealing, deep-defect-level emission disappears and near-band emission is greatly enhanced. Annealed GZO thin films show very low resistivity of 2.6 x 10(-4) Omega .cm with 3.9 x 10(20)/cm(3) carrier concentration and exceptionally high mobility of 60 cm(2)/V.s. These improved physical properties are explained in terms of the translation of doped-Ga atoms from interstitial to substitutional sites.
Keywords: ZINC-OXIDE FILMS; DEPOSITION; SAPPHIRE; EPITAXY; PLASMA; AL